Spin momentum-locked surface states in metamaterials without topological transition - Peng, Liang (2019)
The photonic analogy of the quantum spin Hall Effect, that is, a photonic topological insulator (PTI), is of great relevance to science and technology in optics based on the promise of scattering‐free surface states. The challenges in realizing such scattering‐free surface states in PTIs and other types of symmetry‐protected topological phases are the result of the exact symmetry needed for creating a pair of time reversal pseudo‐spin states or special boundary conditions, wherein the exact symmetry imposes strict requirements on materials or boundary conditions. Here, it is experimentally demonstrated that scattering‐free edge states can be created with neither the aforementioned exact symmetry requirements for materials nor the topological transitions. This system is constructed by simply placing together regular homogeneous metamaterials, which are characterized by highly different bianisotropies. Of the particular surface states, backward reflection would be deeply suppressed, provided that the related evanescent tail into the bulk regions vanishes shortly and that the pseudo‐spin is not flipped by the scatterers. This work gives an example of constructing scattering‐free surface states in classical systems without strict symmetry protections and may potentially stimulate various novel applications in the future.